Optimalisasi Media Sosial Untuk Meningkatkan Citra Koperasi di Kalangan Generasi Z - Audinta Fischela, Delphia; Farida, Farida (Universitas Koperasi Indonesia, 2024)
Cooperatives, in building relationships with the community, do not rely solely on face-to-face interactions but can also establish connections through social media. Platforms like Instagram have the potential to change public perceptions of cooperatives. An institution’s image can be shaped when individuals see or recall something related to the organization. Content associated with an institution or company can create a unified perception among the public toward that organization. Cooperatives can leverage this to build a positive image via Instagram. This research aims to explore the perception of cooperatives among Generation Z and identify managerial strategies that can be employed to build a positive image of Credit Union Rahastra among Generation Z using Instagram. A case study method was employed, with descriptive qualitative data analysis. The findings indicate that while Generation Z, both members, and non-members, have been aware of cooperatives since their school years, they do not fully understand the true nature of cooperatives. Moreover, public relations strategies via Instagram to enhance the positive image of cooperatives, particularly among Generation Z, using the RACE (Research, Action, Communication, Evaluation) framework, have not been fully implemented. Greater commitment is needed to manage the Instagram account effectively.